NGSP and IFCC-derived NGSP HbA1c can be used interchangeably - K. Paisooksantivatana (2018)
Aim: To evaluate comparability of NGSP-certified method and IFCC-calibrated method. Methods: HbA1c was measured on two analyzers (n = 50). Comparability was tested by Deming regression, bias estimation and Friedman test. Results: A strong correlation and good agreement between two methods was demonstrated. Conclusion: NGSP and IFCC-derived NGSP HbA1c can be used interchangeably. © 2009 Elsevier Ireland Ltd. All rights reserved.